Structural and Phase Transformations in 0.3С-1Cr-1Mn-1Si-Fe Steel after Electrolytic Plasma Treatment; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Kozlov E. Eduard; Popova N. Natalya; Zhurerova L. Lyaila; Nikonenko E. L. Elena Leonidovna; Kalashnikov M. P. Mark Petrovich; Skakov M. Mazhin (2016, 2016)
Title screen